Effectiveness Test of Robusta Coffee (Coffea cenephora) Extract from North Sumatra in Collagen and Hydration Skin Level of Female Wistar Rattus norvegicus - Girsang, Lora Coarnita; Fachrial, Edy; Lister, I Nyoman Ehrich (American Scientific Research Journal for Engineering, Technology, and Sciences, 2020)
Robusta coffee (Coffea canephora) is one of the Indonesian plants that have antioxidant compounds that can be used as cosmetic ingredients. The antiaging effect of the coffee extract can overcome the photoaging problem. The purpose of this study is to see the anti-aging effects of robusta coffee bean extract based on concentration variations of the female white rats. The study was conducted in a laboratory with pre and post control group design, from February to March 2019. 30 female white rats were divided into 5 groups and were sunbathed for 5 days, then were shaved 2x2 cm wide on the back and were given Robusta coffee bean extract cream 2.5%, 5%, 7.5%, 10%, and control. Applying cream twice a day for 4 weeks and changes were measured every 1 week for 4 weeks with a skin analyzer. The results were tested for the normality with the Shapiro-Wilk test and Levene's test. Then followed by Anova Repeated, Pearson Correlation and Multiple Linear Regression test. Data analysis was using SPSS 21.0. There were the highest increased of collagen and hydration levels with Coffea canephora 10% extract given, and variable concentrations and duration of administration have a positive effect. The highest increased of collagen level was in the Coffea canephora 10% extract with an average 91.3% and hydration level amounted to 86.09%.